1999
DOI: 10.3109/02841859909175580
|View full text |Cite
|
Sign up to set email alerts
|

Imaging of Abdominal Neuroblastoma in Children

Abstract: Imaging may be a valuable basis for clinical assessment and pretreatment staging of abdominal neuroblastoma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
33
1
1

Year Published

2003
2003
2015
2015

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(37 citation statements)
references
References 26 publications
2
33
1
1
Order By: Relevance
“…MRI has advantages in evaluating the extent of a primary tumor and a possible vessel encasement and in determining operability [3,4,[24][25][26]. In our study, the sensitivity of MRI (86%) was markedly higher than its specificity (77%).…”
Section: Discussioncontrasting
confidence: 56%
See 3 more Smart Citations
“…MRI has advantages in evaluating the extent of a primary tumor and a possible vessel encasement and in determining operability [3,4,[24][25][26]. In our study, the sensitivity of MRI (86%) was markedly higher than its specificity (77%).…”
Section: Discussioncontrasting
confidence: 56%
“…In the literature, comparative studies about the diagnostic value of MIBG scintigraphy and MRI in staging neuroblastoma in pediatric patients have been published [4,14]. The basis of any staging procedure is the detection of single tumor lesions.…”
Section: Pfluger Et Almentioning
confidence: 99%
See 2 more Smart Citations
“…However, there were cases where CT/MR imaging identified a tumour that was not detected by other methods. Previous work has shown that CT and MR imaging are superior to ultrasound in detecting abdominal neuroblastoma; both CT and MR assessed tumour size and location equally well 11. For thoracic tumours, MR imaging appears to be the single most useful test for detecting nodal, intraspinal and chest wall involvement 12.…”
Section: Discussionmentioning
confidence: 99%